If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(-4v+2)-7v=3(v-3)-7
We move all terms to the left:
-7(-4v+2)-7v-(3(v-3)-7)=0
We add all the numbers together, and all the variables
-7v-7(-4v+2)-(3(v-3)-7)=0
We multiply parentheses
-7v+28v-(3(v-3)-7)-14=0
We calculate terms in parentheses: -(3(v-3)-7), so:We add all the numbers together, and all the variables
3(v-3)-7
We multiply parentheses
3v-9-7
We add all the numbers together, and all the variables
3v-16
Back to the equation:
-(3v-16)
21v-(3v-16)-14=0
We get rid of parentheses
21v-3v+16-14=0
We add all the numbers together, and all the variables
18v+2=0
We move all terms containing v to the left, all other terms to the right
18v=-2
v=-2/18
v=-1/9
| −3(x−8)+8=5(x+7) | | 40+1/3+(x-10)+(x-20)=360 | | -9y+6=-7y-6 | | -9r+8r+12=-18+4r | | 5x-203=47 | | 3x-21=15x-69 | | 0.8x=375 | | 13=31.7-3x | | -12=3(j-16)+-18 | | (x-5)=5x=3 | | -12-4x=-2(3x+5) | | 6(3n-4)=36 | | ,25x+4=3 | | 7-6h=16-19h+12h | | 60=4x-5 | | (5x-24)=(3x+24) | | -8u+6=5-9u | | 29+6n=5(1+2n) | | 4(-3x-1)=-(x—) | | 1.2x=375 | | -3(2x-4)=-4x+12-2x | | -8x+2(x-4)=-2 | | 2(-4+2)+5x-2=-19 | | -9u-2+7u=-u-20 | | 2u^2-11u+12=0 | | -8=4+u/3 | | 1+2n=1+7n-5n | | 2.5x-15=60 | | 4(2-8n)=-152 | | 4(j-15)=12 | | 5/8x+2/5=1 | | -7m+6=-36 |